SUPERVISION OF THE FINANCIAL SERVICES AUTHORITY IN THE FIELD OF INVESTMENT IN THE BANKING INDUSTRY BY AN INSURANCE COMPANY - Susanto, Wirawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
The role of OJK in the financial services sector is expected to be able to protect the interests of consumers from losses due to services in the financial sector, one of which is Jiwasraya insurance. Problems arise when OJK's supervision of Jiwasraya's insurance is poor, so they don't know that Jiwasraya's insurance has failed to pay due to accounting engineering (window dressing) since 2006, resulting in losses for Jiwasraya insurance customers. The problem in this research is how is the implementation of supervision by the Financial Services Authority in the investment sector in the banking industry by insurance companies? The research method used is normative juridical using secondary data and analyzed using qualitative methods. The results show that the implementation of supervision by the Financial Services Authority in the investment sector in the banking industry by insurance companies still has weaknesses such as the limited supervision held by the Financial Services Authority at the regional level which does not carry out direct supervision, so the central level Financial Services Authority only carries out supervision and examination of reports that have been recapitulated from all branch offices and regional offices of the concerned financial services business actor. This supervision has the potential for unrecognizing violations of investment in the banking industry by insurance companies, as happened in the Jiwasraya case.